Authority And Responsibility Of Notaries In Making Marriage Agreement Deed - Dominiqy Injili Edfiene Pungus; Gunardi Gunardi (Jurnal Indonesia Sosial Teknologi, 2023)
This study discusses the authority and responsibility of notaries in making marriage agreement deeds. The purpose of this study is to describe and analyse the authority and responsibility of notaries in making marriage agreement deeds and the urgency of marriage agreements. This research method uses normative law because it is based on a statute approach and a conceptual approach. The result of this study is that the notary's authority in making the marriage agreement deed he made is limited to the content of the agreement that has fulfilled the conditions for the validity of the agreement under Article 1320 of the Civil Code, so he cannot be prosecuted in court; conversely, if the marriage agreement certificate does not meet the requirements of the validity of the agreement, then the deed made by a notary can be cancelled by the judge. The notary's responsibility in the marriage agreement is to ensure that no third party is harmed by the making of a marriage agreement after the marriage.